Arqueologia como pedagogia da história em Michel Foucault - Nascimento, Victor Wladimir Cerqueira (2016)
This thesis aims to analyze Michel Foucault's basic principles of pedagogy of history in "archaeological period", which is developed in the writings of the 1960s and whose starting point is Madness and Civilization (1961). It is used as primary sources the works, articles, conferences, and other writings of the author produced until 1961; as a secondary source, the tradition of commentators and biographers. In the first section, we seek to draw up an introductory, from a reflection that is dispersed in the author's work, the sense of a pedagogy of history, ie clarify their conception of history and the role it plays in formation of people. The second section breaks of problematizations that arise from the confrontation of the writings of the French philosopher and education, appropriations that educationalists make of his work, to make a critical assessment of this tradition. The third section is a literature review of how the historiographical field analyzes Foucault's work, giving it the most diverse labels (mentalities, cultural history, etc.) and removing the specificity of archeology. The fourth section demonstrates how the historicity regime emerges in the work of Foucault through an intense debate between phenomenology, history of science, particularly in the history of psychology, and psychoanalysis. This debate is constituted as a starting point to a particular interpretation that the author makes of the Kantian philosophy, present in its complementary thesis Genesis and structure of Kant's Anthropology (1961), and establishing the fundamental principles of its historiographical route. The fifth section is an analysis of how these principles come to embody the archaeological method in Madness and Civilization (1961), demonstrating how the story on the one hand, operates a system of exclusion which is based on rationalism of Western culture and, on the other, reveals a discursive structure and social practices of a historical period - hardly a history of continuous progress and humanization through the acquisition of "scientific truth", the story introduces discontinuities, structures, speeches revealing the conditions of possibility knowledge of an era. The last section concludes that the emergence of the archaeological program puts an intense debate between the history of science, phenomenology and structuralism, and Foucault's pedagogy of history operates from the historical a priori and file description, a critical radical philosophical anthropology and its historiographical counterpart focused on the idea of the subject of the story - rather than constitutive of history, man is first made from her.